1991
DOI: 10.1038/eye.1991.14
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative alterations of the commensal eye bacteria in contact lens wear

Abstract: SummaryA study was performed on the commensal external eye flora in 34 long-term contact lens wearers and a matched control group, in order to identify the effect of lens wear.Samples were taken from the lid margin and conjunctiva by semi-quantitative, and tear film by quantitative methods. Cultured bacteria were identified with particular attention to coagulase-negative staphylococci. No qualitative alteration in the com mensal bacteria was found, although lens wearers were found to have a significantly highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 12 publications
3
28
0
Order By: Relevance
“…Studies of effects of other contact lens use on normal flora have reported conflicting results. Similar to our findings, Fleiszig and Efron 21 reported a decrease in CNS in the conjunctivas of rigid gas permeable extended wear users, but both Larkin and Leeming 22 and Erdogan et al 23 found no increase in the number of conjunctival microbes. In contrast, Iskeleli et al reported an increase in CNS after the use of extended wear silicone hydrogel lenses.…”
Section: Discussionsupporting
confidence: 93%
“…Studies of effects of other contact lens use on normal flora have reported conflicting results. Similar to our findings, Fleiszig and Efron 21 reported a decrease in CNS in the conjunctivas of rigid gas permeable extended wear users, but both Larkin and Leeming 22 and Erdogan et al 23 found no increase in the number of conjunctival microbes. In contrast, Iskeleli et al reported an increase in CNS after the use of extended wear silicone hydrogel lenses.…”
Section: Discussionsupporting
confidence: 93%
“…8,9 Normal ocular biota include CNS, Corynebacterium, Micrococcus, Bacillus, and Propionibacterium species. 40,43,[71][72][73][74][75] In the LASH study, the five most commonly isolated organisms associated with a CIE were Serratia marcescens, Pseudomonas aeruginosa, viridans group streptococci, Corynebacterium species, and CNS. Although some of these organisms are considered normal microbiota, our results suggest that they can initiate an immune response when found in high numbers on contact lenses worn in a static continuous-wear environment.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore obvious that there are controversies about the effect of soft contact lenses on ocular microbiota and the associated diseases. Many authors reported that asymptomatic lens wear for extended periods did increase ocular microbiota (Larkin et al, 1991;Hart et al, 1993) and others reported that asymptomatic lens worn for extended periods did not increase normal ocular microbiota (Gopinathan et al, 1997;Willcox et al, 1997). However, Efron et al (2005) suggested that ocular diseases of contact lens wearer could be as a result of noncompliance or omission of surfactant cleaning rub and rinse steps, the use of disinfecting solution of marginal efficacy and lenses that attract and rapidly deposit protein.…”
Section: Discussionmentioning
confidence: 97%